Greek Resurrection Beliefs and the Success of Christianity - Endsjø, D. author. aut Link
X, 274 p.
Keywords: This book examines the relationship between the growth of Christianity in Greece and the belief in resurrection from the dead. It gives a clear presentation of various generally unknown aspects about traditional Greek religion, such as stories about people being made physically immortal and the Greek fascination with the flesh.